Protein Tau: Prime Cause of Synaptic and Neuronal Degeneration in Alzheimer's Disease. (8th June 2012) - Crespo-Biel, Natalia; Theunis, Clara; Van Leuven, Fred
Abstract : The microtubule-associated protein Tau (MAPT) is a major component of the pathogenesis of a wide variety of brain-damaging disorders, known as tauopathies. These include Alzheimer's disease (AD), denoted as secondary tauopathy because of the obligatory combination with amyloid pathology. In all tauopathies, protein Tau becomes aberrantly phosphorylated, adopts abnormal conformations, and aggregates into fibrils that eventually accumulate as threads in neuropil and as tangles in soma. The argyrophilic neurofibrillary threads and tangles, together denoted as NFT, provide the postmortem pathological diagnosis for all tauopathies. In AD, neurofibrillary threads and tangles (NFTs) are codiagnostic with amyloid depositions but their separated and combined contributions to clinical symptoms remain elusive. Importantly, NFTs are now considered a late event and not directly responsible for early synaptic dysfunctions. Conversely, the biochemical and pathological timeline is not exactly known in human tauopathy, but experimental models point to smaller Tau-aggregates, termed oligomers or multimers, as synaptotoxic in early stages. The challenge is to molecularly define these Tau-isoforms that cause early cognitive and synaptic impairments. Here, we discuss relevant studies and data obtained in our mono- and bigenic validated preclinical models, with the perspective of Tau as a therapeutic target.